Quantitative Proteomic Analysis Reveals the Sites Related to Acetylation and Mechanism of ACY-1215 in Acute Liver Failure Mice - Zhang, Wen-bin; Zhang, Hai-yue; Wang, Yao; Jiao, Fang-zhou; Wang, Lu-wen; Gong, Zuo-jiong (Frontiers in Pharmacology, 2019)
Background: ACY-1215 is a well-known selective histone deacetylase 6 (HDAC6) inhibitor, and it has been considered as a potential therapeutic drug in inflammatory diseases including acute liver failure (ALF). However, little is known about the impact of ACY-1215 treatment on histone lysine acetylation and proteome in ALF. In this study, we aim to investigate whether ACY-1215 has inhibitory effects and mechanism on the necrosis of hepatocytes, moreover, the impact of ACY-1215 treatment on histone lysine acetylation still need further elucidate. Methods: Male C57/BL6 mice were divided into normal, model, and ACY-1215 groups. ACY-1215 (25 mg/kg) and same amounts of saline were injected intraperitoneally to mice before the establishment of ALF model induced by LPS (100 μg/kg) combined with D-gal (400 mg/kg). All animals were sacrificed after 24 h. In this study, detection programs including quantitative proteomic analysis, transmission electron microscopy (TEM) micrographs, pathological staining, protein expression as well as biochemical. Results: The function of liver and the necrosis of hepatocytes in ALF mice were significantly normalized by ACY-1215 pretreatment. The quantitative proteomic analysis revealed that ACY-1215 restrained oxidative phosphorylation by normalized the function respiratory electron-transport chain in mitochondria. Moreover, pretreatment of ACY-1215 not only normalized the structure of mitochondria, but also inhibited the generation of ROS. Conclusions: ACY-1215 was able to inhibit necrosis of hepatocytes in ALF mice through regulating the mitochondrial-mediated oxidative stress, and we identified the common sites related to acetylation level.